Nilai-Nilai Pendidikan Moral Akhlak Masyarakat Melayu - Nyayu Soraya; Maryam Maryam; Syarnubi Syarnubi; Zulhijra Zulhijra (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The purpose of this study was to determine the relevance of moral education in the Malay folklore Gurindam Dua Belas by Raja Ali Haji with moral education in an Islamic perspective. This research uses library research, which the object of the study uses library data in the form of books as the data source. reading, reviewing, and analyzing various existing literature, using the content analysis analysis method. i.e. analyzing the text. The results of the study show that the value of moral education for the people of Malay Gurindam Dua Belas by Raja Ali Haji is found in the third, fourth, sixth and tenth stanzas which contain the value of moral education about the morality of life for someone who wants his own safety by protecting his whole body from all over the world. actions that can lead to mistakes, the importance of a relational relationship and the morality and morals of children to parents and the moral obligations of parents to their children. The value of moral education is also contained in Malay folklore, namely in the abstinence and the tradition of selikur/seven likur which gives a deep meaning to them so that the moral education contained therein can be carried out by instilling Islamic nuances since he was small and this can be attached or always become their memory to carry it out when they are adults.